Sales of immovable property in terms of the National Credit Act 34 of 2005 and the Alienation of Land Act 68 of 1981 - Renke, Stefan (University of Pretoria, 2024)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2024.